PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR IPA DAN RASA PERCAYA DIRI (SELF ESTEEM) PADA SISWA SMPN 6 AMLAPURA - ., I KETUT SUARTIKA; ., PROF. DR. I WAYAN SANTYASA, M.Si.; ., DR. I WAYAN SUKRA WARPALA, S.PD.,M.Sc (Jurnal Teknologi Pembelajaran Indonesia, 2017)
Tujuan penelitian ini adalah mendeskripsikan pengaruh model pembelajaran: 1) hasil belajar IPA dan rasa percaya diri (self esteem) antara siswa yang belajar dengan Model Kooperatif Jigsaw dengan siswa yang belajar dengan Model Pembelajaran STAD, 2) hasil belajar IPA antara siswa yang belajar dengan Model Pembelajaran Kooperatif Jigsaw dengan siswa yang belajar dengan Model Pembelajaran STAD, 3) self esteem antara siswa yang belajar dengan Model Pembelajaran Kooperatif Jigsaw dengan siswa yang belajar dengan Model Pembelajaran Pembelajaran STAD. Eksperimen semu ini dilakukan dengan pre-test-post-test only control group design. Populasi penelitian adalah siswa kelas VII SMP Negeri 6 Amlapura tahun pelajaran 2015/2016 yang berjumlah 5 kelas dengan jumlah siswa 131 orang. Sampel penelitian ditentukan dengan teknik simple random sampling. Sampel yang terpilih adalah Kelas VII B sebagai kelompok eksperimen dengan perlakuan Model Kooperatif Jigsaw, dan Kelas VII A sebagai kelompok kontrol perlakuan Model Pembelajaran Kooperatif STAD. Data hasil belajar siswa dikumpulkan dengan tes hasil belajar yang telah divalidasi, sedangkan data rasa percaya diri siswa dikumpulkan dengan kuisioner self esteem siswa yang sudah divalidasi. Data hasil belajar awal dan sikap ilmiah awal dikumpulkan sebelum eksperimen, dan data hasil belajar dan sikap ilmiah dikumpulkan pada akhir perlakuan. Data dianalisis dengan statistik deskriptif dan Uji MANCOVA yang dilanjutkan dengan Uji LSD. Uji signifikansi dilakukan pada taraf 5%. Hasil penelitian menunjukkan: 1) Hasil belajar IPA dan self esteem siswa yang belajar dengan model pembelajaran kooperatif Jigsaw lebih baik daripada siswa yang belajar dengan model pembelajaran kooperatif STAD, 2) hasil belajar IPA siswa yang belajar dengan model pembelajaran kooperatif Jigsaw lebih baik daripada siswa yang belajar dengan model pembelajaran kooperatif STAD, 3) Self esteem siswa yang belajar dengan model pembelajaran kooperatif Jigsaw lebih baik daripada siswa yang belajar dengan model pembelajaran kooperatif STAD. Kata Kunci : Model Kooperatif Jigsaw dan STAD, Hasil Belajar, Self Esteem The aim of the research was to describe and analysis the difference of: 1) student’s achievement and their self esteem between whom learned by cooperative Learning Model Jigsaw with student who learned by cooperative Learning Model STAD, 2) student’s achievement between student who learned by cooperative Learning Model Jigsaw with student who learned by cooperative Learning Model STAD, 2) self esteem between student who learned by cooperative Learning Model Jigsaw with student who learned by cooperative Learning Model STAD. This quasi experiment was conduvted by pretest-post test only control design. Population of this research was 5 classes of 7th grade student of SMP Negeri 6 Amlapura in the years 2015/2016 which consisted of 131 person. Sample of the research determined by simple random sampling technique towards already matched class. The sample that has been choosen was VII B class as experiment group which was learned using cooperative Learning Model Jigsaw, and VIII A class as control group which was learned using cooperative Learning Model STAD.Dependent variable that is analyzed is student’s learning achievement and self esteem. Student’s learning achievement data took by student’s learning achievement test that already been validated, meanwhile student’s self esteem data took by student’s self esteem questionaire that already been validated. The data of prior achivement and prior students’ self esteem were collected befor intervention and the data of students’ achievement and their self esteem were coleccted after treatment. All of the data were analysed descriptively and MANCOVA test and continued by LSD test. To test the research hyphothesis, the 5% of significance different was used. The research findings show that: 1) student’s achievement and their self esteem between whom learned by cooperative Learning Model Jigsaw was better than student’s who learned by cooperative Learning Model STAD, 2) student’s achievement between student who learned by cooperative Learning Model Jigsaw was better than student who learned by cooperative Learning Model STAD, 3) self esteem between student who learned by cooperative Learning Model Jigsaw was better than student who learned by cooperative Learning Model STAD, 3). keyword : Jigsaw learning model and STAD learning model, students’ achievement, students’ self esteem.